On the Road towards Grand Inclusivity: The Development of Japan’s Treatment towards Its Disability Community’s Security - Abel Josafat Manullang; Sudrajat, Jasson Aditya; Excel Stephen (Jurnal Transformasi Global, 2023)
Apart from their advanced technological innovation and development, Japan is also known for its support towards its disability community. However, Japan has a long and interesting history behind it as it initially, and to some degree in the present, did not appear that way. Filled with discrimination and even ostracization, Japan has gone a long distance to its present supportive treatment. By using the qualitative research method based on secondary data, the article aims to shed light to 4 issues. First, the article begins by laying out Japan’s background regarding their treatment towards the disability community. Here, it can be seen how in the past they were subjected to confinement and discrimination. Moving on, a discussion over the changes of treatment towards them by the government is provided. The changes can be attributed to the government’s rational move to uphold human security, strive towards a more inclusive society, and preparation towards huge events like the 2020 Tokyo Paralympics. The way the government made such changes is through the securitization or speech act. Eventually, the changes materialised into many forms, from the supportive bills/laws all the way to infrastructure adjustments that would ease access for people with disabilities on the field. Finally, for the implications brought about by the changes, it can be seen in how the environment are more accessible for people with disability and how it can work as a public diplomacy attempt as apparent in the 2020 Tokyo Paralympics. Keywords: Human Security, Inclusive Society, Japan, Disability.